The Story of Noble Rot - Uzma Aslam Khan (New Delhi Rupa & Co., 2009)
It is the careless abandon of a wine-satiated afternoon that first brings together the imperious Mrs. Masood and the humble carpenter's wife, Malika. As she observes the wealthy woman whose family is responsible for all her troubles, a plan takes shape in Malika's mind to recover the money Mrs. Masood owes her husband, and rescue her son from slow death in Mr. Masood's carpet factory. Unknown to both women, the moment marks the beginning of relationship that is to change their lives forever. Vividly narrated and full of funny yet complex dilemmas, this is a novel about the sweetness of life and about how we inexorably drive ourselves to our own doom. It marks the debut of a gifted storyteller from Pakistan.
English Fiction.
Keywords: Rug and carpet industry -- India -- Affluent consumers